Analisa Kelayakan Finansial Proyek Pembangunan Apartemen The Peak Pekanbaru - Mathofani, Anna; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru as the capital of Riau province which has strategic location, its making thegovernment has a vision to make pekanbaru city as the third metropolitan city in theisland of Sumatra. One of the keys of success in achieving Pekanbaru's vision is thegrowing of properties development. The Peak apartment building project that presents aconcept that combines apartments and hotels and built for the housing needs of thecommunity that is safe, comfortable and strategic located. The construction investment inthis project needs a high cost, so it needs feasibility analysis of financial. Indicators ofinvestment feasibility using method BCR (Benefit Cost Ratio), NPV (Net Present Value),IRR (Internal Rate of Return), BEP (Break Even Point) and Sensitivity Analysis. Theresults of investment calculation in this research is Rp. 153.455.919.352,57, by using aninterest rate of 13.25% is obtained value of BCR = 1.35, NPV = Rp. 70.430.609.438,07,IRR = 28,90%, the value of BEP = 5 years and 4 months (age = 20 years of the projectplan) and the value of the investment sensitivity analysis increased by 140%, thesensitivity of benefit decreased by 61%, sensitivity of cost increased by 246% and interestrate sensitivity increased by 28,90%, with the results of the investment feasibility analysisfrom described above, so all the parameters indicate the scope for appropriateinvestment.Keywords: Feasibility Analysis of Financial, Investment , Pekanbaru , The PeakApartment, Sensitivity Analysis,